Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 11 - Additional Topics - Chapter 11 Review Problem Set - Page 520: 51



Work Step by Step

We first use the FOIL method to simplify the expression. Then, knowing that $i=\sqrt{-1}$, we can substitute $-1$ for $i^{2}$ to obtain: $(-3-3i)(7+8i)$ =$-3(7+8i)-3i(7+8i)$ =$-21-24i-21i-24i^{2}$ =$-21-45i-24i^{2}$ =$-21-45i-24(-1)$ =$-21+24-45i$ =$3-45i$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.